Endocytic trafficking of chemokine receptors - Marchese, Adriano (Curr Opin Cell Biol, 2013)
Chemokine receptors belong to the super family of G protein-coupled receptors (GPCRs). The cognate ligands for chemokine receptors are small circulating proteins known as chemokines. Upon binding to their cognate chemokines, receptors are rapidly desensitized, internalized onto early endosomes and sorted either into a recycling pathway or degradative pathway. Chemokine receptor trafficking is essential because it limits the magnitude and duration of signaling by removing receptors from the cell surface thereby limiting access to their ligands, but it also delivers bound chemokines to lysosomes for degradation. Once on endosomes receptors are sorted into a recycling pathway contributing to resensitization of receptor signaling or they are sorted into the degradative pathway leading to long-term attenuation of signaling. Recent studies have revealed some key information regarding the molecular determinants mediating chemokine receptor internalization and have shed light on the mechanisms dictating sorting into either the recycling or degradative pathways. Here I discuss our current understanding of the mechanisms mediating chemokine receptor trafficking with a focus primarily on recent findings for the chemokine receptor CXCR4.